(untitled) (Research, Society and Development, 2020)
The association between drugs and nutrients enables the development of undesirable interactions, leading to an increase or reduction of drug and nutrient efficacy. Interaction between drugs and nutrients is considered when a particular food or nutrient alters the efficacy of a drug, or when there is interference with the patient’s nutritional status. This study aimed to highlight through a literature review the drug-nutrient interactions in hospitalized pediatric patients. This is a literature review of the narrative type, for its construction we used the following databases: Scielo, VHL and Google Scholar. At the hospital level, food and pharmacological therapy are essential for health recovery and stabilization, and attention needs to be given to drug-nutrient interaction, as this interaction may decrease or increase the efficacy of medicines and / or foods. , impair the nutritional status, aggravate the clinical condition, and increase the length of hospitalization, especially in children who constitute a highly vulnerable age group.